2011
DOI: 10.1021/jp109054j
|View full text |Cite
|
Sign up to set email alerts
|

A Simple QM/MM Approach for Capturing Polarization Effects in Protein−Ligand Binding Free Energy Calculations

Abstract: We present a molecular simulation protocol to compute free energies of binding, which combines a QM/MM correction term with rigorous classical free energy techniques, thereby accounting for electronic polarization effects. Relative free energies of binding are first computed using classical force fields, Monte Carlo sampling, and replica exchange thermodynamic integration. Snapshots of the configurations at the end points of the perturbation are then subjected to DFT-QM/MM single-point calculations using the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
162
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(164 citation statements)
references
References 95 publications
0
162
0
Order By: Relevance
“…7), which would give a QTCP-like approach. Similar corrections have been used in similar contexts before [68][69][70][71][72][73][74]. Unfortunately, such an approach becomes unstable if the differences between the MM and QM potentials are too large, leading to corrections that depend only in a few of the DFT calculations [90].…”
Section: Fep Results At the Dft-d3 Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…7), which would give a QTCP-like approach. Similar corrections have been used in similar contexts before [68][69][70][71][72][73][74]. Unfortunately, such an approach becomes unstable if the differences between the MM and QM potentials are too large, leading to corrections that depend only in a few of the DFT calculations [90].…”
Section: Fep Results At the Dft-d3 Levelmentioning
confidence: 99%
“…We use two types of approaches to get around this problem and still retain the rigorousness. The first type is an endpoint approach, previously applied in reference-potential methods such as QM/FEP, QTCP (QM/MM thermodynamic cycle perturbation), and paradynamics [68,69,70,71,72,73,74]. Here, a thermodynamic cycle is used to obtain…”
Section: Dft-d Fep Calculationsmentioning
confidence: 99%
“…Beierlein et al 15 use the difference between the Coulombic contribution to the interaction energy and Fox et al 23 use the full quantum interaction energy where they perform Density Functional Theory (DFT) calculations on the whole ligand-solvent system using the ONETEP linear-scaling DFT program. 24 Interaction energies are defined by:…”
Section: Figure 1: Extended Thermodynamic Cycle For Computing Free Enmentioning
confidence: 99%
“…For small ligands, this results in about 400 water molecules described by DFT while for the ASP-SER and LYS-SER complexes this results in about 700 DFT water molecules. In light of this observation, results obtained with previous QM/MM approaches 11,45,50 which treat only the solute by QM and the solvent by MM would need to be re-examined as for example calculations of free energies and other properties using these approaches may be dominated by the variation (noise) that the interaction energies have when zero or a very small number of quantum waters are included. We expect that one of the first applications of our embedding approach will be in schemes for the calculation of free energies of binding of biomolecular assemblies with full inclusion of charge transfer and polarisation effects via large-scale DFT calculations.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly useful in this context is the ability to accurately calculate interaction energies as these can be used to obtain Gibbs free energies of binding which are essential in drug design. A variety of methods are available for this such as the recent approach by Beierlein et al 45 who have demonstrated via a series of careful tests how the free energies obtained via a classical force field can be converted to free energies that would be obtained if a quantum description was used for the ligand and classical force field for the surrounding atoms. The mutation from the classical to the quantum state happens via a one-step free energy perturbation formula (the Zwanzig equation), as follows:…”
Section: A Interaction Energiesmentioning
confidence: 99%